2017
DOI: 10.1016/j.jpeds.2017.08.074
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Neonatal Resuscitation Program–Recommended Low Oxygen Strategy on Outcomes of Infants Born Preterm

Abstract: Objective To evaluate the impact of the Neonatal Resuscitation Program (NRP) recommended low oxygen strategy on neonatal morbidities, mortality and neurodevelopmental outcomes in preterm neonates. Study design In March 2011, Parkland Hospital changed from a high oxygen strategy (HOX) of resuscitation with initial 100% O2 and targeting 85–94% SpO2 for delivery room (DR) resuscitation to a low oxygen strategy (LOX) with initial 21% O2 and titrating O2 to meet NRP recommended transitional target saturations. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 50 publications
0
32
0
1
Order By: Relevance
“…Additional subgroup analyses that evaluated the effect of varying the definition of low and high oxygen concentration (21%À30% compared with 80%À100% only; 30% compared with 90%À100%; 50% compared with 100%; 30% compared with 60%À65%) and whether SpO 2 targeting as a cointervention had any impact found no differences in primary and secondary outcomes. 10 When data from 2 observational cohort studies with 1225 newborns 182,183 were pooled, initiating resuscitation with lower oxygen was associated with a statistically significant benefit in long-term mortality for all preterm newborns and the subgroup of 28 weeks' gestation (RR, 0.77 [95% CI, 0.59À0.99]; I 2 = 6%). 10…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Additional subgroup analyses that evaluated the effect of varying the definition of low and high oxygen concentration (21%À30% compared with 80%À100% only; 30% compared with 90%À100%; 50% compared with 100%; 30% compared with 60%À65%) and whether SpO 2 targeting as a cointervention had any impact found no differences in primary and secondary outcomes. 10 When data from 2 observational cohort studies with 1225 newborns 182,183 were pooled, initiating resuscitation with lower oxygen was associated with a statistically significant benefit in long-term mortality for all preterm newborns and the subgroup of 28 weeks' gestation (RR, 0.77 [95% CI, 0.59À0.99]; I 2 = 6%). 10…”
Section: Consensus On Sciencementioning
confidence: 99%
“…In addition to the RCTs, a total of 4437 patients were included in 4 observational cohort studies ranging from 125 to 2326 patients. 27,33,35,36 The studies were from Australia, Canada (n = 2), and the United States and were published between 2009 and 2017 with patient recruitment from 2004 to 2012. Oxygen saturation targeting was included as a cointervention in all of these observational studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Researchers in 2 studies compared initiating resuscitation with Fio 2 1.0 (before) to resuscitation with Fio 2 0.21 (after). 27,35 Researchers in the other 2 studies compared initiating resuscitation with Fio 2 1.0 (before) to 2 "after" cohorts: either Fio 2 0.21 or an intermediate oxygen concentration of Fio 2 0.22 to 0.99. 33,36 For these latter 2 studies, only the room air and Fio 2 1.0 groups were used because the intermediate groups had a range of starting oxygen levels and could not be classified as low or high.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biochemical and clinical outcomes described by Vento et al (26), were similar to those found in preterm infants in the high oxygen strategy group who exhibited significantly higher values for oxidative stress biomarkers and had a higher incidence of ventilator days and BPD (23). Kapadia et al (28), recently published the follow up results of their study (27), and showed that the lower oxygen strategy was associated with improved respiratory morbidities and neurodevelopmental outcomes with no increase in mortality (28). Tataranno et al (29) and Kato et al (30) in blood and urine analysis, respectively, also found that using FiO 2 of 1.0 significantly increased biomarkers of protein, lipids and DNA oxidation in preterm infants <32 weeks' gestation using high performance liquid chromatography coupled to mass spectrometry.…”
Section: Studies Supporting the Use Of Lower Initial Inspired Oxygenmentioning
confidence: 99%